Hungry bone syndrome secondary to prostate cancer successfully treated with radium therapy. (6th July 2018) - Garla, Vishnu Vardhan; Salim, Sohail; Kovvuru, Karthik Reddy; Subauste, Angela
Abstract : A 50-year-old man with a history of prostate cancer with extensive bone metastasis and hypocalcaemia presented with muscle aches and cramps. Physical exam was significant for Chvostek's and Trousseau's sign. Laboratory assessment was consistent with profound hypocalcaemia. This was believed to be due to hungry bone syndrome secondary to advanced prostate cancer. He was treated with intravenous calcium, vitamin D and calcitriol. He also received three doses of radium 223 therapy. After therapy, hypocalcaemic episodes resolved. Follow-up after 2.5 years showed continued resolution of hypocalcaemia.